Integrated genomic analysis of antibiotic resistance and virulence determinants in invasive strains of Streptococcus pneumoniae - Liu, Lin; Wang, Yanfei; Ge, Lihong; Hu, Dongping; Xiang, Xi; Fu, Ying; Lu, Jun; Li, Xi; Yu, Yunsong; Tu, Yuexing; Wu, Xueqing (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Streptococcus pneumoniae is an important human pathogen that may cause severe invasive pneumococcal diseases (IPDs) in young children and the elderly. A comprehensive comparative whole-genome analysis of invasive and non-invasive serotype strains offers great insights that are applicable to vaccine development and disease control. Methods In this study, 58 invasive (strains isolated from sterile sites) and 71 non-invasive (serotypes that have not been identified as invasive in our study) pneumococcal isolates were identified among the 756 pneumococcal isolates obtained from seven hospitals in Zhejiang, China (2010–2022). Serotyping, antimicrobial resistance tests, and genomic analyses were conducted to characterize these strains. Results and discussion The three most invasive serotypes were 23F, 14, and 6B. The invasive pneumococcal isolates' respective resistance rates against penicillin, ceftriaxone, tetracycline, and erythromycin were 34.5%, 15.5%, 98.3%, and 94.7%. Whole-genome sequencing indicated that the predominant invasive clonal complexes were CC271, CC876, and CC81. The high rate of penicillin non-susceptible Streptococcus pneumoniae (PNSP) is related to the clonal distribution of resistance-conferring penicillin-binding proteins (PBP). Interestingly, we found a negative correlation between invasiveness and resistance in the invasive pneumococcal serotype strains, which might be due to the proclivity of certain serotypes to retain their β-lactam resistance. Moreover, the mutually exclusive nature of zmpC and rrgC+srtBCD suggests their intricate and potentially redundant roles in promoting the development of IPD. These findings reveal significant implications for pneumococcal vaccine development in China, potentially informing treatment strategies and measures to mitigate disease transmission.